REFORMASI POLITIK DAN EKONOMI DI MYANMAR PADA MASA PEMERINTAHAN PRESIDEN U THEIN SEIN (2011-2013) - Devi Apriyanti; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Political and economic rerform in Myanmar during the regimeof President U Thein Sein year 2011-2013. The research aims to determine why the government of U Thein Sein do the political and economic reform in Myanmar, and to know the efforts to realize it. The hypothesis of the research that the reform conducted because of the authoritarian government, the lack of enforcement in human right, the weak and unstable economy, and the lack of labor freedom and press. This research used qualitative research methods with explanation analysis methods. Data collection techniques used are library research techniques. Based on the data obtained by the researchers that the government of President U Thein Sein have big influence in doing the political and economic reform in Myanmar and creating more democratic country. The things that have been realized in the field of politics are enforcement of human right, cabinet reshuffle, abolition of media cencorship, freedom of speech and association for labor, and release of political prisoners. In the economy field, there are economic liberalization and legal guarantees for foreign investors.Key Word: Myanmar, Reform, Democracy, Economy, Political